Tinjauan Urgensi Manajemen Kesiswaan Terhadap Prestasi Belajar Peserta Didik - Ristianah, Niken (Kartika: Jurnal Studi Keislaman, 2023)
Student management is a process of managing all matters relating to student in a school starting from planning student admission, coaching carried out while students are at school, until students complete their education at school throught creating a learning atmosphere that is condusive to the on going learning process affective teaching or learning. With student management, institutions can organize student affairs both in terms of student need, recruitment, selection, orientation, class placement, and coaching and development of students both in curricular and extracurricular and more importantly recording and reporting of graduation result, and recording of student who continue other education and alumni. The generalobjective of student management is to regulate all activities related to students so that these activities can support the teaching and learning process in schools, so that activities can run smoothly, orderly, and can contributed to achieving school goals and overall education goals